راده ی بایهخپێدانی بهرنامه گفتوگۆییهكان به پهتای كۆرۆنا بهرنامهی (تاوتوێ)له کهناڵی nrt به نموونه توێژینه وهیه کی شیکارییه - ن, به ناز حه مهره شید حه سه (Sulaimani Journal for Humanities, 2021)
This paper is titled The main aim of this study is to find out “How talk shows covered Covid-19 Outbreak: NRT Tawtwe Talk Shaw as a case” This paper consists of three key sections, the first segment is about the research theoretical framework, which focuses on research problem, aims of the research, importance of the research, the methodology of the research, limitations, community and research sample, research tools and research terms as well. The second section of the research is focuses on tv programs, tv program types, talk show programs and the presenter of talk shows. The last section of this research is the practical section, the results and recommendations of the research will be explained.
Keywords: Television program; covid19; tawtwe program; talkshow